Pendidikan Multikulturalisme di Pondok Pesantren Al Hidayah Sebagai Strategi Pencegahan Paham Radikalisme dan Terorisme - Manda Prayogi; Sakti Ritonga (LPPM Universitas Ekasakti Padang, 2023)
This study aims to find out how to prevent radicalism and terrorism through understanding multiculturalism education at Al-Hidayah Sei Mencirim Islamic Boarding School. As a theoretical basis in analyzing the problems in this qualitative research, theories about radicalism, terrorism and multicultural education are used, so that researchers are required to obtain data and information by conducting indepth interviews and observations. This research uses a qualitative approach that is descriptive. The informants in the study were Buya Ghazali who served as the leader of the Al-Hidayah Sei Mencirim Islamic Boarding School, Ummi Ksrtini Banurea and Ummi Putri who worked as teachers at the Al-Hidayah Sei Mencirim Islamic Boarding School. The data collection technique used by researchers is by conducting interviews, observation and documentation, using a phenomenological study approach, namely researchers trying to find meaning from the phenomenon of preventing radicalism and terrorism through understanding multiculturalism education at the Al-Hidayah Sei Mencirim Islamic Boarding School. School. The data analysis used in this research is descriptive analysis, which summarizes all the data that has been collected from the interviews. The results of this study indicate that multiculturalism education can prevent the development of radicalism and terrorism. With multiculturalism education, the students of Al-Hidayah Mencirim Islamic Boarding School can understand the importance of tolerance and mutual respect for differences according to Islamic law.